PERINATAL OBSTETRIC OUTCOMES IN WOMEN WITH RHESUS-NEGATIVE BLOOD. - U.U. Jabborov, Y.G. Rasul-Zade (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research focuses on the analysis of perinatal outcomes in women with rhesus-negative blood at the Republican Perinatal Centre in one year. Materials and methods: The analysis was carried out on 341 women with rhesus-negative blood who were delivered at the perinatal center in one year. The women were divided into 4 groups. Group 1: 71 women who delivered baby with rhesus-negative blood. The 2nd group 225 women who delivered babywith rhesus-positive blood without increasing the titer of antibodies, the 3rd group 28 women who delivered babywith hemolytic disease of a newborn and the 4th group 18 women with rhesus immunization, but who underwent antenatal operation "Intrauterine intravascular blood transfusion to the fetus". Research results: During the year it was revealed that the incidence of HDN was only 0.84% of all women born in the perinatal center, while the rate of HDN development in Rhesus-negative pregnant women was 14.0%. Conclusion: The conducted antenatal "intrauterine intravascular blood transfusion to the fetus" in the 4th group (where 85.4% of newborns with low body weight) contributed to the decrease in the birth of newborns with severe asphyxia by more than 2.5 times.